TUGAS KESEHATAN KELUARGA PADA ANGGOTA KELUARGA YANG MENDERITA TB PARU - Herawati; Kausar, Lola Illona Elfani; Pertiwiwati, Endang (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2015)
Pulmonary Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis bacteriawhich attacks the lung. Family health task is an obligation that should be performed by a family inorder to optimize the health of the family members. The role of family is very significant in preventingthe transmission and in assisting the patient during treatment that proper implementation of familyhealth task is extremely required. The purpose of this study was to described the family health tasksto family member(s) suffering from Pulmonary Tuberculosis in the working area of Astambul PublicHealth Center in the period from February-August 2014. The method used in this study was adescriptive research method. There were 30 respondents taken with saturated sampling technique.The results of the study on the implementation of family health tasks showed that: 8 respondents(26%) were categorized good, 11 respondents (37%) fair, and 11 respondents (37%) poor. The resultsof the performance of each task indicated that identifying problems was 15 respondents (50%) poor,making decision 18 respondents (60%) fair, providing treatment 15 respondents (50%) poor,modifying the environment 13 respondents (43%) fair, and utilizing the health facilities 12respondents (40%) good. It could t be concluded that the implementation of family health tasks tofamily member(s) suffering from pulmonary tuberculosis in the working area of Astambul PublicHealth Center in the period from February-August 2014 mostly fell under the category of fair andpoor.